Utworzenie kategorii godności człowieka (dignitas hominis) przez Hieronima ze Strydonu - Guerrero van der Meijden, Jadwiga (Vox Patrum, 2023)
This article discusses the emergence of the anthropological-axiological category of human dignity in the writings of Jerome of Strydon. In order to estimate’s Jerome’s originality, the article analyses his sources: writings of Origen of Alexandria and Cicero’s De officiis. Pointing out the watershed moment in the history of European thinking on human dignity, when Jerome created a systematically applied name for the axiological status of human beings, dignitas hominis, allows us to undermine the findings so far operating in the scientific debate, which point to authors such as Augustine of Hippo or Leo the Great as pioneers in the application of the category of “human dignity.” Showing that the category of dignitas hominis was used for the first time around the year 397 by a Bethlehem’s hermit thus postpones by several decades the first systematic occurrence of the concept of human dignity in European culture.